La explotación de materiales pétreos dentro de la legislación ecuatoriana, su cumplimiento y control - Collahuazo Pilaquinga, Edwin Paul (2016)
This research proposal for consideration by the National University of Loja and the general public arises from the need to analyze the problem titled "MATERIAL PETREOS FARM LEGISLATION IN ECUADOR COMPLIANCE AND CONTROL", and especially with regard to consultation with indigenous communities in the mining concessions, social problem has been given due to the lack of legal regulation in order to establish the parameters for the exploitation of aggregates and stone materials from the beds of the rivers without due consultation with the residents of the areas where mining is performed whose indiscriminate use is causing the effects on the environment and surroundings; is why it is necessary to develop mechanisms or structure our mining legislation according to the social reality that includes this problem. I approach from the point of social, legal terms, and analyzing historical in its national and international context, to develop a reform or legal reform project which somehow will help address this social and historical phenomenon. From the point of view of environmental impact is the alteration of the environment as a result of the completion of mining activities with respect to the situation that would exist if not taken action on the matter as this environmental impact would produce changes in the environment health problems that affect the population and the historical value that have stocks of these sectors. Mining activities have led to many environmental problems. One of the main and most affected was the water has changed its course with the surrounding land erosion producing, polluting being unfit for human and animal consumption and plant what should worry more that are extinct rivers and streams. We must consider that in the economy of our country is of great importance since mining has been developed in different regions of Ecuador there providing different kinds of mining raw materials for industry and then consumer demand for our country. Why you should make a conscious mining, respecting nature protecting our resources in primary water is essential for life on the planet resource.